Answer:
![f^(-1)(x) = 2x - 8\\ f^(-1)(4) = 0](https://img.qammunity.org/2019/formulas/mathematics/college/cgxqterqk8yzz6vl8wkn47jkrf5kt5no1k.png)
Explanation:
To find an inverse function, we need to think the function as an equality x = 1/2y + 4 that we have to resolve for the y.
First, let's subtract 4 from both sides.
x - 4 = 1/2y + 4 - 4
x - 4 = 1/2y
Now we multiply by 2 on both sides.
(x-4)*2 = 1/2y*2
2*x-8 = y
Therefore, the inverse function is
![f^(-1)(x)=2x-8](https://img.qammunity.org/2019/formulas/mathematics/college/h6xlhjshp9y3ccxoypzgswiezdzx2untmz.png)
To find out
, we need to replace the x of the function with a 4:
= 2*4 - 8 = 8 - 8 = 0
= 0